Quality Assurance and The Philippine Education System: Inputs From Future Filipino School Leaders - Inero V. Ancho (Jurnal Penjaminan Mutu, 2019)
This study involves future education leaders and managers in the Philippines and their conceptual understanding of “quality” in the context of education, the streams of teaching and learning to be specific. Respondents were enrolled in a graduate program in a teacher education institution based in Manila, Philippines and were asked the following: (1) concepts identified with quality; (2) conceptual understanding of quality assurance; (3) quality assurance mechanisms employed in the Philippine education system; and (4) proposed quality assurance mechanisms to uplift the academic achievement of Filipino students. It has been revealed that while future education leaders and managers possess sufficient ideas and knowledge about quality assurance, it is still vital to provide them with technical know-how and discourses on the theoretical-practical connection of quality and students’ academic achievement. Quality assurance mechanisms being implemented are considered to be effective in the Philippine education system.